FAKTOR YANG MEMPENGARUHI PENGETAHUAN IBU TENTANG PEMENUHAN KEBUTUHAN NUTRISI PADA IBU NIFAS - Dwiharini Puspitaningsih (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
Knowledge about nutritional needs influence the selection of food and fulfillment the needs of postpartum mothers nutrition to defend the body against infection and begin the process of lactation. The purpose of this study was to know the factors that predisposed the mother's knowledge about the nutritional needs fulfillment of postpartum mothers. Type of research was descriptive quantitative research. The research variables are factors that predisposed the mother's knowledge about nutritional needs fulfillment of postpartum mothers (age, education, parity, employment and economic status). The population was 18 post partum mothers with number of sample was 18 respondents. The sampling technique used was total sampling. This study was conducted in Tunggal Pager, Pungging,Mojokerto on 7-14 April 2015. The data was collected using a questionnaire. Data was analyzed using frequency distribution. The results showed that nearly half of respondents aged 20-35 years who had a good knowledge as many as 8 respondents (44.4%), high school-educated respondents had a good knowledge as many as six respondents (33.3%), multiparous had good knowledge as many as five respondents (27.8%), the un employment or housewife had a good knowledge as many as seven respondents (38.9%) and respondents who had an income <UMR (Rp 2.695.000,-). Age is the most dominant factor behind the good mother knowledge about the fulfillment of the nutritional needs of postpartum mothers in Tunggal Pager Pungging Mojokerto. It is expected that post partum mothers may be motivated to eat a balanced diet to meet the nutritional needs during childbirth